Business Strategy Analysis at PT Kimia Farma (Persero) Tbk. Using Business-Level Strategy - Adi Neka Fatyandri; Angel Angel; Desi Pratama; Michelle Go; Nicholas Sunaidi; Shirlyn Shirlyn (Jurnal Ilmu Manajemen Profitability, 2024)
In facing the dynamics of the pharmaceutical industry which continues to develop, PT Kimia Farma (Persero) Tbk. has taken strategic steps by implementing a business-level strategy to differentiate itself from competitors. As a leading pharmaceutical company in Indonesia, PT Kimia Farma tries to answer the increasing demand for medicines and health services by implementing differentiation and cost leadership strategies. Despite facing challenges in cost leadership, this company has succeeded in covering its shortcomings by providing various innovations and variations in health services, including 24-hour pharmacies and health consultation services through the Kimia Farma Mobile application. The company's long history, which was founded in 1817, as well as the establishment of four subsidiaries with specific focuses, has become a strong foundation for PT Kimia Farma to achieve its goal of becoming a leading health company that continues to integrate and generate sustainable value. Even though there are problems in determining drug costs and competition with similar companies, the company's differentiation strategy remains the main attraction by providing superior services to the Indonesian people. For the future, companies are advised to continue expanding service variety, optimizing cost leadership, and maintaining focus on innovation-based strategies to ensure sustainable growth in an increasingly complex pharmaceutical industry.